Prolonged acetogenic phase and biological succession during anaerobic digestion using swine manure - Bonugli-Santos, Rafaella Costa; Marteres, Tiago Joelzer; Luiz, Franciele Natividade; Somer, Juliana Gaio; Mari, Ângelo Gabriel; Passarini, Michel Rodrigo Zambrano (Folia microbiologica, 2022)
In recent years, global warming and the limitation of fossil fuels have been causing the governments of different countries to think about the search for more sustainable fuel sources. Biomethane (CH4) has gained increasing attention in recent years as an alternative option for a sustainable source of energy. Biogas is generated during the anaerobic digestion of organic materials by the metabolism of complex microbial communities in the substrates that make up this digestion. The microbial community evaluation using 16S rDNA metabarcoding in a bench covered pond bioreactor using swine effluent revealed the dominant bacteria belonging to Firmicutes, Proteobacteria, and Bacteroidetes phyla. The methanogenic group was represented by the Euryarchaeota phylum. It was possible to observe that the relative frequency of the methanogenic archaea community decreased with the anaerobic digestion, indicating a biological succession stage. On the other hand, there was a predominant acetogenic diversity in this final stage. These data showed stabilization of biomethane production, although the microbial community of methanogens has drastically reduced in the late process.
Keywords: Animals; ribozomální DNA; DNA, Ribosomal; fosilní paliva; Biofuels; prasata; Fossil Fuels; hnůj; Archaea; Manure; methan; Swine; Methane; Bioreactors; Anaerobiosis; zvířata; anaerobióza; biopaliva; bioreaktory